Modernization of Professional Training of Electromechanics Bachelors: ICT-based Competence Approach - Євгеній Модло; Сергій Семеріков; Катерина Шмельцер (Освітній вимір, 2018)
Modlo Yе.O., Semerikov S.O. and Shmelttser K.O. Modernization of Professional Training of Electromechanics Bachelors: ICT-based Competence Approach.